Contemporary Housing Struggles A Structural Field of Contention Approach - Florea, Ioana; Gagyi, Agnes; Jacobsson, Kerstin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This OA book provides a comparative study of housing contention in Budapest and Bucharest in 2008-2021. The financialization of housing and the resulting inequalities, expulsions and social contention are a central characteristic of today$1 (Bs capitalist crisis. These two East European cities that fall outside the usual focus of urban movements research provide an illuminating case of similar structural conditions governed by different political constellations at the national and local scales. Instead of searching for unilinear narratives connecting structural tensions to politicized claims, the book offers an in-depth contextual analysis of multiple forms of contention, their (often unintentional) interactions, and their broader political-structural background, including tensions surrounded by political silence. The authors analyze the two cases and their comparative lessons through what they propose as a (3z(Bstructural field of contention(3y (Bapproach to the multiple, interconnected ways in which structural tensions become (or not) politicized in today$1 (Bs social movements. The book will appeal to everyone interested in today$1 (Bs urban tensions and social movements. .s
1. Introduction. Embedding the Analysis of Housing Contention in the Sociopolitical Complexity of Structural Crises -- 2. The Structural Field of Contention Approach -- 3. The Structural Background of Housing Contention in Bucharest and Budapest -- 4. Housing Contention in Budapest -- 5. Housing Contention in Bucharest -- 6. Structural Fields of Contention in Housing Struggles. Comparative Lessons -- 7. Conclusion.
Keywords: Social policy; Sociology, Urban; Economic sociology; Comparative Social Policy; Urban Sociology; Economic Sociology